Involvement of Fluids in Earthquake Ruptures Field/Experimental Data and Modeling - Yamashita, Teruo (Springer Japan, 2018)
This book furnishes state-of-the-art knowledge about how earthquake faulting is coupled with fluid flow. The authors describe the theoretical background of modeling of faulting coupled with fluid flow in detail. Field and laboratory evidence to suggest the fluid involvement in earthquake faulting is also carefully explained. All of the provided information constitutes together a basic framework of the fault modeling for a comprehensive understanding of the involvement of fluids in earthquake ruptures. Earthquake generation is now widely believed to be significantly affected by high-pressure fluid existing at depths. Consequently, modeling study of earthquake faulting coupled with fluid flow is becoming increasingly active as a field of research. This work is aimed at a wide range of readers, and is especially relevant for graduate students and solid-earth researchers who wish to become more familiar with the field.